Implementasi Program Keluarga Harapan (PKH) dalam Meningkatkan Kesejahteraan Masyarakat Kecamatan Rumbio Jaya - Masrul Ikhsan; Hafzana Bedasari; Ahmad Hadi (Bahasa Indonesia, 2022)
The purpose of this study was to describe the Implementation of the Family Hope Program (PKH) in Improving the Welfare of the Communities of Rumbio Jaya District and to find out the inhibiting and supporting factors. The method in this study is Policy Research (Policy Research) with a Qualitative Descriptive approach. The research location is in Rumbio Jaya District, Kampar Regency, Riau. Primary data was obtained through interviews, while secondary data was obtained through a literature search that was appropriate to the research topic. Data analysis in this study used data analysis techniques developed by Miles Huberman. The implementation of the Family Hope Program (PKH) in Improving Community Welfare in Rumbio Jaya District has been successful. Then the supporting factors in the implementation of PKH also get support from stakeholders. While the inhibiting factors are jealousy from people who are not PKH recipients and the absence of facilities such as loudspeakers for loudspeakers when giving directions.